Penerapan Petri Net Pada Layanan Antrian di SPBU Kota Gorontalo - Barham, Siti Maryam; Yahya, Lailany; Payu, Muhammad Rezky Friesta; Nurwan, Nurwan (Research in the Mathematical and Natural Sciences, 2023)
This study aims to apply Petri Net for queuing services for gas stations in the city of Gorontalo. The subject that became the focus of the research was the Jalan Jendral Sudirman gas station. The results obtained in this application are 11 places and 11 transitions, a matrix representation of the model, and the convertibility tree model.